(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2010)
The organic walled dinoflagellate cyst Pseudorhombodinium cinguloindentatum gen. et sp. n. is formally described from the Upper Eocene of Sicily, Italy. It consists of a brown coloured, circumcavate wetzelielloid cyst with marked V-shaped cingular indentations in the pericyst. The proposed generic name refers to similarities existing in the overall morphology with the genus Rhombodinium Gocht. However, substantial differences in archeopyle styling, in the disposition of antapical horns, and in the amount of cingular indentation, advocate the erection of the new genus Pseudorhombodinium.